Numerical investigation of inelastic and temperature dependent layered asphalt pavements at loading by rolling tyres. Issue 1 (2nd January 2021) - Wollny, I.; Hartung, F.; Kaliske, M.; Canon Falla, G.; Wellner, F.
ABSTRACT: Understanding the structural behaviour of layered asphalt pavements at loading by rolling tyres is a fundamental requirement for the future design of more durable pavements. The paper presents the framework for a realistic and at the same time efficient numerical investigation of temperature dependent layered asphalt pavements loaded by steady state rolling tyres. Thereby, the temperature dependent behaviour of two asphalt mixes is described by temperature dependent parameter functions, which are identified based on a particle swarm optimisation at hand of experimental data of repeated load triaxial tests. The layered pavement structure and its loading by rolling tyres is captured by a coupled tyre-pavement FE model. The present paper introduces in this context a novel contact interface that enables the use of 20-node quadratic brick elements for the FE pavement model. The coupled tyre-pavement model is applied for an intensive numerical investigation of two pavement structures. Thereby, different pavement temperatures, layer bond properties, driving velocities, tyre loads and tyre inflation pressures are considered and their influence on the resulting displacements, stresses and strains is discussed.